2008
DOI: 10.1051/forest:2007088
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual tree mortality in northern hardwood stands under uneven-aged management in southern Québec, Canada

Abstract: -This study proposes a generalized linear mixed model to predict individual tree mortality in northern hardwood stands under uneven-aged management. The model is based on a complementary log-log (CLL) link function, and was calibrated using permanent-plot data. Tree vigor, stem product, diameter at breast height and stand basal area were tested as explanatory variables. A plot and an interval random effect were specified to account for spatial correlations. When compared with the traditional logit link functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 25 publications
2
57
0
2
Order By: Relevance
“…Other authors have developed parametric regressions (such as logistic regression) using permanent plot data which included both growth (either directly or indirectly through competition indexes) and size to obtain synthetic mortality models including regular and irregular mortality (Eid and Tuhus, 2001;Fortin et al, 2008;Moore et al, 2004;Uriarte et al, 2004;Wunder et al, 2007;Yao et al, 2001). Nevertheless, it has been demonstrated that due to unbalanced data-sets from permanent plots and to the highly skewed shape of mortality, parametric models assuming a strict model shape may lead to biased mortality estimates and wrong interpretations concerning species 305p7 Ann.…”
Section: A Flexible Model Making the Most Of Available Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have developed parametric regressions (such as logistic regression) using permanent plot data which included both growth (either directly or indirectly through competition indexes) and size to obtain synthetic mortality models including regular and irregular mortality (Eid and Tuhus, 2001;Fortin et al, 2008;Moore et al, 2004;Uriarte et al, 2004;Wunder et al, 2007;Yao et al, 2001). Nevertheless, it has been demonstrated that due to unbalanced data-sets from permanent plots and to the highly skewed shape of mortality, parametric models assuming a strict model shape may lead to biased mortality estimates and wrong interpretations concerning species 305p7 Ann.…”
Section: A Flexible Model Making the Most Of Available Datamentioning
confidence: 99%
“…When permanent plot data are available, competition indexes (or growth) and size are often combined in a parametric regression, such as the logistic regression, to determine mortality estimates (Eid and Tuhus, 2001;Fortin et al, 2008;Moore et al, 2004;Uriarte et al, 2004;Wunder et al, 2007;Yao et al, 2001). Parametric functions have two disadvantages when trying to calibrate mortality models.…”
Section: Taking Into Account Both Size-and Growth-dependent Mortalitymentioning
confidence: 99%
“…It was necessary to account in statistical models for this variation in the length of the time interval over which serological transitions were observed. To do so, a complementary log-log link function was used and the log of the length of the time interval was included as an offset in all the models presented below (Fortin et al 2008). Goodness of fit was assessed through Pearson overdispersion test (Bolker et al 2009).…”
Section: Statistical Modelingmentioning
confidence: 99%
“…Indeed, trees in the same plot are likely to be correlated, trees observed in the same period for a plot and observations made on the same tree in a plot-method as well. A cloglog link was used and an offset variable corresponding to the log of time interval between two measurements was included in the model and its coefficient was set to 1 (Fortin et al, 2008;Rose et al, 2006). The general model considered for the five species of interest was:…”
Section: Statistical Analysesmentioning
confidence: 99%